Test The Effectiveness Botanical Insecticide of Citronella Leaf Extract (Cymbopogon nardus L.) to Control Stink Bug (Leptocorisa oratorius Fabricius) on Upland Rice - Desita Salbiah; Eva Maryanti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Leptocorisa oratorius F. is one of the factors causing the decline in rice production. Appropriate and safe control measures for the environment need to be taken, considering that the use of chemical pesticides can have a negative impact on the environment. The treatment solution that can be used to deal with the stink bug pest (Leptocorisa oratorius F.) is by using plant-based pesticides which are known to be relatively safe because they do not pollute the environment and are easy to obtain. A plant that has the potential to be used as a botanical insectiside is citronella (Cymbopogon nardus L). The research aims to obtain a concentration of citronella leaf extract (Cymbopogon nardus L) that is effective in controlling the stink bug pest (Leptocorisa oratorius F.) on rice plants. The research was carried out at the Plant Pest Laboratory and Greenhouse, Faculty of Agriculture, Riau University, which was carried out for three months from Januari to Maret 2023. The research was carried out experimentally using a completely randomized design (CRD) consisting of five treatments and four replications so that 20 experimental units were obtained with various concentrations, namely 0 g.l-1 water, 25 g.l-1 water, 50 g.l-1 water, 75 g.l-1 water, 100 g.l-1 water. The results showed that the application of the stems and citronella leaves extract concentration of 75 gl-1 water is an effective concentration for controlling L. oratorius because it can cause a mortality of 85% with an initial time of death of 17.75 hours after application and a lethal time of 50 at 61.25 hours after application. The exact concentration of peper elder extract to control 50% of Leptocorisa oratorius is 4.31% or the equivalent of 43.1 g.l-1 water.